Conductance Switching and Mechanisms in Single‐Molecule Junctions1. Issue 33 (1st July 2013) - Jia, Chuancheng; Wang, Jinying; Yao, Changjiang; Cao, Yang; Zhong, Yuwu; Liu, Zhirong; Liu, Zhongfan; Guo, Xuefeng
<x xml:space="preserve">Abstract</x> A molecular switch: The conductance of a new molecular device based on graphene–molecule junctions was reproducibly switched between open and closed states under irradiation of external light (see picture). Three photochromic diarylethene derivatives with different substituents were used as key elements of the molecular devices.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>